The value of thermography in the preoperative mapping of primary and recurrent varicose veins - Staszkiewicz, W.; Madycki, G.; Grzegrzólka, J.; Hendiger, W. (Phlebologie, 2000)
Aim: Despite great advances in ultrasound diagnosis of the venous system, there is still a need for a quick and simple method of complex preoperative visualisation of the superficial venous system and its incompetent perforators. The aim of the study was to assess the usefullness of thermography in the preoperative mapping of the superficial venous system among patients with primary and recurrent varicose veins. Method: Authors examined prospectively 48 patients with varicose veins (36 with primary and 12 with recurrent varicose veins). Preoperative assessment was performed by means of infrared scanning (thermography). The results were verified by colour coded duplex ultrasound and intraoperative findings. In the results, the mapping of incompetent veins by thermography unit showed an excellent correlation with colour/duplex scan and intraoperative findings. The sensitivity and specificity for thermography were 85.4% and 93.7% respectively and were lower than the values acquired by US scanning (sensitivity and specificity – 89.6% and 97.7% respectively). Conclusion: Authors conclude, that colour/duplex ultrasound remains a method of choice in the preoperative evaluation of the entire venous system, but thermography offers a simple and quick method for complex mapping of the incompetent superficial venous system. This method might prove to be a helpful adjunct to the ultrasound, particularly in case of recurrent varicose veins or in cases, when the incompetent veins are not well seen (e. g. obesity).
Keywords: Ultrasound; thermography; varicose veins